Immunohistochemical characterisation of inflammatory, neuroimmune and histologically "normal" appendicitis - Psaltis, Emmanouil (2021)
Background Appendicitis is the most common surgical condition, but its diagnosis can be challenging. The practice of early appendicectomy to minimise morbidity and mortality has resulted in an increase of histologically "normal" appendices (HNA) being resected. Even, in the laparoscopic era, the removal of a macroscopically normal appendix in a symptomatic patient remains a clinical dilemma. The discrepancy between the clinical and histological diagnosis could suggest that an unknown pathology exists. This study compared the in-situ expression of key inflammatory markers in HNA resected from symptomatic patients with histologically inflamed samples.